2016
DOI: 10.1515/acve-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Placental Iodothyronine Deiodinases Expression in Pregnant Cows Exposed to Propylthiouracil (Ptu) and Thyroid Axis Activity of their Calves

Abstract: The aim of our study was to investigate if the thyroid axis of newborn calves is affected by prenatal application of propylthyouracil (PTU). The study included 20 late pregnant Holstein cows. One group (n=10) was treated with PTU (4 mg/kg of BW daily) from day 20 before expected calving until the day of calving. The other group (n=10) was non-treated. Placental samples of dams were obtained for measuring mRNA expression of iodothyronine deiodinases type I (D1), type II (D2) and type III (D3). After parturition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The hypothalamic-pituitary-thyroid (HPT) axis plays a consistent role in the growth and development of fetal and neonatal calves [1,2], according to metabolic and non-metabolic mechanisms [3][4][5]. Indeed, thyroid hormones play a crucial role in successful implantation and during the early stages of embryo development [6,7], suggesting a local action of thyroid hormones and thyroid-stimulating hormone (TSH) on both the endometrium and the embryo [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothalamic-pituitary-thyroid (HPT) axis plays a consistent role in the growth and development of fetal and neonatal calves [1,2], according to metabolic and non-metabolic mechanisms [3][4][5]. Indeed, thyroid hormones play a crucial role in successful implantation and during the early stages of embryo development [6,7], suggesting a local action of thyroid hormones and thyroid-stimulating hormone (TSH) on both the endometrium and the embryo [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal thyroid function is under a strong maternal thyroid axis's influence, on the basis of placental permeability for iodine, improving fetal thyroid hormone synthesis [13,14]. Nevertheless, there is no evidence about thyroid hormones transfer through the ruminants' placenta [2]. During the physiological development, thyroid changes dynamically occur, according to genetic and non-genetic factors, nutritional intake [15], environmental stimuli [16], and deiodinases' expression [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of maternal hypothyroidism on offspring health are important in human [1] and veterinary medicine [2]. Previously, in the rat model, we have shown that maternal hypothyroidism during pregnancy and lactation leads to premature ovarian failure of pubertal and adult offspring [3].…”
Section: Introductionmentioning
confidence: 99%
“…This selenoprotein converts T4 to T3 by deiodination of the outer ring, and it can convert T3 and T4 into the inactive T2 or rT3, respectively, via inner ring deiodination [46]. Given the primary localization and function of DIO1, it is not unsurprising that we were unable to detect a measurable concentration of mRNA encoding this protein in CAR samples; however, it should be noted that previous studies have shown DIO1 to be abundant in the term placenta [47], which may be associated with circulating concentrations of T3 being highest at parturition [47,48].…”
Section: Selenoproteinsmentioning
confidence: 68%